Development of residential schools for indigenous minorities in Canada – selected problems - Tomasz Gmerek (Studia z Teorii Wychowania)
The article deals with the issue of the relation between education and the processes of assimilation and discrimination of indigenous minorities (Indians and Inuit) in Canada. Particular emphasis was placed on reconstructing educational practices and the educational policy that is implemented toward indigenous minorities within Canadian school system (especially destruction of their ethnic identity in residential schools). An attempt was made at examining the relationship between schooling, religion, socialization, forced Christianization, language policy, and the development of aboriginal minorities in Canada.